AN ANALYTICAL STUDY ON THE TENSIONAL INTEGRITY OF AN EXISTING DIAGRID STRUCTURAL SYSTEM - Amirudin, Ashikin Mastura (Universiti Teknologi PETRONAS, 2020)
This work centers on the interrelationship between the diagrid structural system and the tensional integrity system. As the emergence of tall buildings, structural design for high rise towers are governed by wind load and seismic load thus becomes the focal point in maintaining the buildings stability under strong horizontal forces. Diagonalised grid structures, diagrids, has a unique set of diamond, triangulated shape that can withhold external forces and maintains stability of the building. However, it is a very complicated structure that is highly prone to rectification work and has little to no deviation between the columns and the nodal joints. Hence, to compensate the complexity of the structure, adopting cable-strut assemblies for tension in cables and compression in bars, tensegrity system, is carried out in this work.